Strategies for achieving and maintaining green ICT campus for Malaysian higher education institutes - Alla K.R.; Chen S.D. (American Scientific Publishers, 2023)
It is very essential for Mankind to reduce the dependency on fossil oils as the reserves are limited and being consumed at staggering rate within this Century and it is high time to look for alternate, renewable energy sources. Every Organization and Individual need to commit and be responsible for building a society that is aware of the situation and move towards clean and green energy. This paper focuses on the importance and the strategies that are to be kept in place for making and maintaining Green ICT Campus for Malaysian Higher Education Institutions in this direction. 2017 American Scientific Publishers All rights reserved.